Using Phragmites australis(Iraqi plant) to remove the Lead (II) Ions form Aqueous solution. (Baghdad Science Journal, 2017)
Lead remediation was achieved using simple cost, effective and eco-friendly way from industrial wastewater. Phragmitesaustralis (P.a) (Iraqi plant), was used as anovel biomaterial to remove lead ions from synthesized waste water. Different parameters which affected on adsorption processes were investigated like adsorbent dose, pH, contact time, and adsorbent particle size, to reach the optimized conditions (maximum adsorption). The adsorption of Pb (?) on (P.a) involved fast and slow process as a mechanism steps according to obey two theoretical adsorption isotherms; Langmuir and Freundlich. The thermos dynamic adsorption parameters were evaluated also. The (?H) obtained positive value that meanes adsorption of lead ions was an endothermic processwhile (?G)values were negative which means that adsorption of lead ions was a spontaneous process and the decrease in (?G) with temperature increasing revealed that lead ions adsorption on (P.a) became favorable with temperature increasing